Effectiveness of a Peer-Led Web-Based Intervention to Improve General Self-Efficacy in Using Dating Apps Among Young Adults: Randomized Clustered Trial - Wong, William CW; Sun, Wai Han; Chia, Shu Ming Cheryl; Tucker, Joseph D; Mak, William PH; Song, Lin; Choi, Kitty Wai Ying; Lau, Stephanie Tsz Hei; Wan, Eric Yuk Fai (JMIR Publications, 2020)
BackgroundOnline dating apps are popular platforms for seeking romance and sexual relationships among young adults. As mobile apps can easily gain access to a pool of strangers ("new friends") at any time and place, it leads to heightened sexual health risks and privacy concerns. ObjectiveThis study aimed to evaluate the effectiveness of a peer-led web-based intervention for online dating apps to prepare Chinese college students so that they have better self-efficacy when using dating apps. MethodsAn open clustered randomized controlled trial was conducted among students from three colleges (The University of Hong Kong, Hang Seng University of Hong Kong, and Yijin Programme of Vocational Training College) in Hong Kong. Students aged 17 to 27 years who attended common core curriculum or general education were randomized into intervention and control groups. The intervention material, developed with high peer engagement, included four short videos, an interactive scenario game, and a risk assessment tool. An existing website promoting physical activities and healthy living was used as a control. Using the information, motivation, and behavioral skills (IMB) approach to design the evaluation, questionnaires covering participants' sociodemographics and dating app characteristics, as well as the general self-efficacy scale (GSE) as the primary outcome and the risk propensity scale (RPS) as the secondary outcome were administered before, immediately after, and at 1 month after the intervention. Intention-to-treat analysis was adopted, and between-group differences were assessed using the Mann-Whitney U test. A post-hoc multiple linear regression model was used to examine the correlates of the GSE and RPS. ResultsA total of 578 eligible participants (290 in the intervention group and 288 in the control group) participated in the study with 36 lost to follow-up. There were more female participants (318/542, 58.7%) than male participants in the sample, reflecting the distribution of college students. Over half of the participants (286/542, 52.8%) reported the following reasons for using dating apps: being curious (170/498, 34.1%), trying to make new friends (158/498, 31.7%), and finding friends with similar interests (121/498, 24.3%). Overall, the participants in the intervention group reported favorable experiences when compared with the finding in the control group. There was significant improvement in the GSE score and reduction in the RPS score (P<.001) in the intervention group. University of Hong Kong students were more susceptible to risk reduction after the intervention when compared with students from the other two institutions. ConclusionsThe online intervention was effective in improving general self-efficacy and reducing risk tendency among young students. Future work is needed to determine if this approach is cost-effective and such behavioral change is sustainable. Trial RegistrationClinicalTrials.gov NCT03685643; https://clinicaltrials.gov/ct2/show/NCT03685643. International Registered Report Identifier (IRRID)RR2-10.1186/s13063-018-3167-5